Breaking the bounds : - Evans, Gillian Rosemary (Cambridge University Press, 2004)
In this impassioned and challenging lecture, the author addresses the interdisciplinary nature of the study of medieval texts and its inherent problems, drawing important lessons for teaching and research within the modern university.